The Binding Power of Underhand Business Contracts in Trade Practices - Mulyani Santoso (LP2M IAIN Palopo, 2026)
Business contracts are an important instrument in trade practices, serving as the basis for legal relationships between parties. In practice, many business contracts are drawn up underhand for efficiency and flexibility. However, the use of underhand contracts often raises legal issues, particularly regarding their binding force and evidentiary validity in the event of a dispute. This study aims to analyze the binding force of underhand business contracts in trade practices and their implications for legal certainty for the parties. This research employs normative legal research methods with both a statutory and conceptual approach. Data were obtained through a literature review of laws and regulations, legal doctrines, and literature relevant to contract law and evidence. Qualitative analysis was conducted by interpreting legal norms related to the validity and binding force of agreements. The research results show that underhand business contracts have legally binding force as long as they meet the requirements for a valid agreement as stipulated in the Civil Code. The main difference between underhand contracts and authentic deeds lies in the evidentiary aspect, not in the validity of the agreement. Underhand contracts have perfect evidentiary force if acknowledged by the parties, but require additional evidence in the event of a denial. Therefore, the use of underhand business contracts remains relevant in trade practice, but requires caution in their formulation to ensure legal certainty and protection. Keywords: business contracts, underhand agreements, binding force, proof, trade practices.